The Contribution of Translation to the Formation of Themes of 'city' and 'women' in the Social Novel in ‘Poetics Proper’ of the Late Qajar Era (1895–1925) - Saidi, Maryam; Manafi Anari, Salar (Iranian Journal of Translation Studies, 2020)
Social novel emerged in ‘poetics proper’ of the late Qajar era and was established in Persian literary system during Pahlavi. In this genre, ‘city’ and ‘women’ constitute the dominant themes. Applying the ‘Model for the Analysis of Translation Poetics’, the present study attempted to investigate the contribution of translation to the emergence of the social novel in ‘poetics proper’ of the late Qajar era (1313-1344AH/1275-1304SH). Firstly, based on the most important literary histories and bibliographical lists of translations of this period, main tenets of ‘poetics proper’ were identified and it was found that social novel can be categorized under ‘fictional literature patronized by the press system and publishing houses/publishers to be produced with the critique-reform function’. Then, 333 translations were investigated and it was illustrated that translation of travelogue and police-detective novels contributed the theme of ‘city’ to this genre, translation of Rousseau’s works drew writers’ attention to the theme of ‘city’ in contrast to the ‘country’, and translation of women biographies/stories, women’ educational-legal literature and women’s translation practices in women’s press played an important role in writing about ‘women’s’ problems. Moreover, the present study showed that the way these themes were dealt with in social novels of the late Qajar era, compared to the way they were considered during pre-Constitution, found a new emphasis that the view toward ‘city’ and ‘women’ was no longer ‘ideal-romantic’, but more realistic along with elements of ‘negative/dark romanticism’. Hence, during the late Qajar toward Phalavi I, urbanization and modernization brought corruption and prostitution.